2016
DOI: 10.1016/j.bbmt.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Allogeneic Hematopoietic Cell Transplantation in Children and Young Adults with Chronic Myeloid Leukemia: A CIBMTR Cohort Analysis

Abstract: Chronic myeloid leukemia (CML) in children and young adults is uncommon. Young patients have long life expectancies and low morbidity with hematopoietic cell transplantation (HCT). Prolonged tyrosine kinase inhibitor (TKI) use may cause significant morbidity. In addition indication for HCT in patients in first chronic phase is not established. We hence retrospectively evaluated outcomes in 449 CML patients with early disease receiving myeloablative HCT reported to the CIBMTR. We analyzed various factors affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
(62 reference statements)
3
24
1
Order By: Relevance
“…The quality of life is one of the integral parts of the survival outcomes especially in pediatric populations, which is to a big extent related to the incidence and severity of cGVHD, and we confirmed a significant higher incidence of cGVHD with peripheral blood stem cell source than the marrow source …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The quality of life is one of the integral parts of the survival outcomes especially in pediatric populations, which is to a big extent related to the incidence and severity of cGVHD, and we confirmed a significant higher incidence of cGVHD with peripheral blood stem cell source than the marrow source …”
Section: Discussionsupporting
confidence: 71%
“…As described in the results section, the 5‐year EFS in our study cohort was 80% and was significantly better with peripheral blood stem cell source ( P = .05), but we could not detect an impact of disease stage, time to transplant, and donor gender which was reported among other different studies . Also this study reported total cumulative incidence of relapse of 16%, which was lower than that reported by other pediatric studies, and of interest about 87% of them maintained their molecular remission with salvage therapies post‐transplant …”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…88 With its more aggressive clinical features and evidence of biological and host differences, pediatric CML cannot be easily categorized using adult criteria or treated using adult guidelines. As the only established therapeutic approach that can achieve a lifelong remission in CML, allogeneic BMT may allow pediatric CML patients to avoid lifelong TKI therapy.…”
mentioning
confidence: 99%
“…88,91,93,94 Late outcomes of BMT (.2 years) for CML have been evaluated in the Bone Marrow Transplant Survivor study, 95 although only 5% of the patients were ,21 years of age. In that study, overall health was excellent, very good, or good in 78% of patients.…”
mentioning
confidence: 99%